Organic reactions - Overman, Larry E. (Wiley, 2005)
Organic Reactions is a comprehensive series of volumes composed of chapters devoted to important synthetic reactions. For each volume, the chapter authors are world-renowned experts with extensive hands-on experience in the field. The chemistry is presented from a preparative point of view and particular attention is given to reaction limitations, interfering influences, effects of chemical structure, and the selection of experimental conditions. Each reaction is fully referenced to the primary literature; Numerous detailed procedures illustrate the significant modifications of each method; Includes tables that contain all possible examples of the reaction under consideration.